Community Structure of Bivalve in the Seagrass Ecosystems in the Madong Bay Waters of Bugis Village Tanjungpinang City Riau Islands - Yolanda, Tiwi Novia; Adriman, Adriman; Fajri, Nur El (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTSea grass ecosystem in the Madong Bay is inhabited by numerous aquatic organisms, including bivalve. A research aims to determine the community structure of bivalve in that seagrass ecosystemhas been conducted in July 2019.There were 3 stations, in the rivermouth, in the bay and in the sea. In each station, there were  2transect lines(25 m length), and distance between the line was 15 m. In each line, there were 4 quadrants(1x1 m2). Sampling was conducted twice a week for 2 weeks. Bivalve present inside the quadrant were sampled manually. Results shown that there were 8 bivalve species present, namelyPlacamen chlorotica, Anomalocardia squamosa, Callista lilacina, Circe scripta, Anadara granosa, Semele cordiformis, Trachycardium rugosum, Anadara gubernaculum. The diversity index (H’) was 1.965-2.242, the uniformity index (E’) was 0.356-0.472 and the dominance index (C’) was 0.225-0.262. The water quality parameters are as follows; Temperature was 29-31 0C; acidity (pH) was 7; Salinity was 30-35 ‰; current speed was 0.14-0.15 m/s and DO was 6.7-6.9 mg/L. Keywords:Circe scripta, diversity index, uniformity index, dominance index